CD4 T Cells in Mycobacterium tuberculosis and Schistosoma mansoni Co-infected Individuals Maintain Functional TH1 Responses - McLaughlin, Taryn A.; Khayumbi, Jeremiah; Ongalo, Joshua; Tonui, Joan; Campbell, Angela; Allana, Salim; Gurrion Ouma, Samuel; Odhiambo, Felix Hayara; Gandhi, Neel R.; Day, Cheryl L. (Frontiers in Immunology, 2020)
Mycobacterium tuberculosis (Mtb) is a serious public health concern, infecting a quarter of the world and leading to 10 million cases of tuberculosis (TB) disease and 1.5 million deaths annually. An effective type 1 CD4 T cell (TH1) immune response is necessary to control Mtb infection and defining factors that modulate Mtb-specific TH1 immunity is important to better define immune correlates of protection in Mtb infection. Helminths stimulate type 2 (TH2) immune responses, which antagonize TH1 cells. As such, we sought to evaluate whether co-infection with the parasitic helminth Schistosoma mansoni (SM) modifies CD4 T cell lineage profiles in a cohort of HIV-uninfected adults in Kisumu, Kenya. Individuals were categorized into six groups by Mtb and SM infection status: healthy controls (HC), latent Mtb infection (LTBI) and active tuberculosis (TB), with or without concomitant SM infection. We utilized flow cytometry to evaluate the TH1/TH2 functional and phenotypic lineage state of total CD4 T cells, as well as CD4 T cells specific for the Mtb antigens CFP-10 and ESAT-6. Total CD4 T cell lineage profiles were similar between SM+ and SM- individuals in all Mtb infection groups. Furthermore, in both LTBI and TB groups, SM infection did not impair Mtb-specific TH1 cytokine production. In fact, SM+ LTBI individuals had higher frequencies of IFNγ+ Mtb-specific CD4 T cells than SM- LTBI individuals. Mtb-specific CD4 T cells were characterized by expression of both classical TH1 markers, CXCR3 and T-bet, and TH2 markers, CCR4 and GATA3. The expression of these markers was similar between SM+ and SM- individuals with LTBI. However, SM+ individuals with active TB had significantly higher frequencies of GATA3+ CCR4+ TH1 cytokine+ Mtb-specific CD4 T cells, compared with SM- TB individuals. Together, these data indicate that Mtb-specific TH1 cytokine production capacity is maintained in SM-infected individuals, and that Mtb-specific TH1 cytokine+ CD4 T cells can express both TH1 and TH2 markers. In high pathogen burden settings where co-infection is common and reoccurring, plasticity of antigen-specific CD4 T cell responses may be important in preserving Mtb-specific TH1 responses.